Transcatheter Mitral Valve Implantation (TMVI) Using Edwards SAPIEN 3 Prostheses in Patients at Very High or Prohibitive Surgical Risk: A Single-Center Experience. (9th January 2020) - Werner, Nicolas; Kilkowski, Caroline; Sutor, Dorothee; Weisse, Udo; Schneider, Steffen; Zahn, Ralf
Abstract : Background . Mitral valve surgery in patients with failing bioprosthesis, annuloplasty rings, or in patients with advanced mitral annular calcification (MAC) is associated with high morbidity and mortality rates. Percutaneous antegrade transseptal transcatheter mitral valve implantation (TMVI) has recently successfully been performed in those patients at high or prohibitive surgical risk, but data on patients treated by TMVI are sparse. This study sought to evaluate short- and midterm outcomes of patients treated by TMVI at our site in clinical practice. Methods and Results . From October 2016 to February 2018, seven patients (six women and one man) at high or prohibitive surgical risk underwent TMVI at our site. Three procedures were performed as TMVI in failed mitral valve bioprostheses (TMVI-VIV, "valve-in-valve"), one procedure was performed as TMVI in a failed mitral annuloplasty ring (TMVI-R), and three procedures were performed as TMVI in advanced native mitral annular calcification (TMVI-MAC). Mean age of the population treated was 77 ± 8.1 years, and mean log EuroScore I was 39 ± 0.12%. In all patients, an Edwards SAPIEN 3 transcatheter heart valve was implanted under 3D-TOE and fluoroscopic guidance using a transvenous/transseptal access. Indication for TMVI was the presence of advanced heart failure symptoms in all patients (NYHA class III/IV). The predominant dysfunction of the mitral valve treated was severe regurgitation in 72% ( n  = 5) and severe stenosis in 29% ( n  = 2) of all patients. TMVI was technically successful in all procedures. Clinical success with functional improvement of at least one NYHA class after procedure compared with before procedure was also achieved in all patients. Median NYHA class improved significantly from 4 before procedure to 2 after TMVI (p = 0.008 ). Mitral valve regurgitation was reduced to trace or mild in all but one patient, who showed moderate MR after TMVI-MAC. No patient-prosthesis mismatch or LVOT obstruction occurred after TMVI. Two patients underwent interventional ASD closure during the in-hospital course due to a large and persisting atrial septal defect after transseptal access. One patient underwent pacemaker implantation due to complete AV-block after TMVI. One patient died in hospital 12 days after the procedure due to severe hospital-acquired pneumonia and sepsis. In-hospital mortality rate was 14% (1/7) in this high-risk population. After hospital discharge, no death occurred and clinical improvement—according to NYHA functional class—remained stable during one-year follow-up. Conclusion . In this small single-center series, TMVI appears promising for patients at high or prohibitive surgical risk with either failing mitral bioprostheses/annuloplasty rings or native mitral valve dysfunction in combination with advanced MAC. Gaining experience in TMVI and new valves will further improve safety and efficacy of this new treatment option.